2006
DOI: 10.1177/875697280603700306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Inter-Project Integration-Empirical Analysis in Program Context

Abstract: This exploratory study focuses on the problem of inter-project integration and how the perceived uncertainty and structural complexity affect the importance of different integration mechanisms used. Four case programs from four companies were chosen as a source of empirical data. Data collection in the selected case programs was multifaceted and included in-depth interviews, questionnaires, and documents and archives. Fifteen integration mechanisms were identified and further categorized into five different cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Such IT vendors are increasingly implementing inter-related client projects in the form of programs. From an organizational perspective, programs represent mechanisms that are increasingly used to develop and implement strategic organizational changes, too complex or vague in their objectives to fit into the traditional project management frame (Dietrich, 2006). The implementation of strategic initiatives (Pellegrinelli and Bowman, 1994), the development of organizational capabilities (Pellegrinelli, 1997), and the implementation of complex information systems (Ribbers and Schoo, 2002) are examples of organizational changes introduced by programs (Pellegrinelli et al, 2007).…”
Section: Samplementioning
confidence: 99%
“…Such IT vendors are increasingly implementing inter-related client projects in the form of programs. From an organizational perspective, programs represent mechanisms that are increasingly used to develop and implement strategic organizational changes, too complex or vague in their objectives to fit into the traditional project management frame (Dietrich, 2006). The implementation of strategic initiatives (Pellegrinelli and Bowman, 1994), the development of organizational capabilities (Pellegrinelli, 1997), and the implementation of complex information systems (Ribbers and Schoo, 2002) are examples of organizational changes introduced by programs (Pellegrinelli et al, 2007).…”
Section: Samplementioning
confidence: 99%
“…This study is therefore the first study to provide quantitative evidence for the performance relevance of project lineage management. Previous studies have centered on the importance and coordination of concurrent project interdependencies in portfolios (Killen, 2013; Killen & Kjaer, 2012; Kopmann, Kock, Killen, & Gemünden, 2015; Teller et al, 2012) or programs (Dietrich, 2006; Hoegl & Weinkauf, 2005; Hoegl, Weinkauf, & Gemünden, 2004). We contribute to this research by also showing the relevance of coordinating temporal interdependencies.…”
Section: Discussionmentioning
confidence: 99%
“…Research repeatedly indicates that although there are common elements such as financial measures, strategic checklists or portfolio visualisation techniques in many PPM processes; each organisation must customise and adapt their PPM process to their individual situation (see for example Cooper et al, 2001, Killen et al, 2008, Loch, 2000. Empirical research has also shown that PPM capabilities are an important mechanism for alignment of project activities with strategy (Dietrich, 2006, Milosevic and Srivannaboon, 2006, Poskela et al, 2005.…”
Section: Ppm Capabilitiesmentioning
confidence: 99%